Pengembangan Bahan Ajar Bahasa Indonesia SMP Kelas VIII Melalui Kajian Teks 88 Kisah Kebijaksanaan Tiongkok Kuno Karya Andy Chow 2015 - Muryati, Ika, Drs. Agus Budi Wahyudi, M. Hum (2016)
This study aims to: (1) Determine what are the text in Acts 88 Ancient Chinese Wisdom Andy Chow's work in 2015 which can be used as material development junior class VIII. (2) Describe the implementation of the text 88 Ancient Chinese Wisdom Story Andy Chow's work in 2015 that can be used as teaching material in the junior class VIII. The method used is qualitative descriptive. Objects in this study text wisdom tale story of 88 ancient Chinese works of Andy Chow, 2015. The data source text of this study all 88 stories of ancient Chinese wisdom works of Andy Chow, 2015. The data in this study a 88 story text wisdom of ancient Chinese works of Andy Chow 2015 corresponding to Indonesian teaching materials junior class VIII. Data collection techniques used in this research is to see the engineering and technical notes. Mechanical Analysis of data using a unified method, a method that is used or to determine the identity of a particular lingual unit by using the tool determinants that are beyond language, regardless of the language, and does not become part of the language concerned. Presentation of the results of data analysis techniques in the form of rules that can be presented through two methods: informal and formal methods. The results of the study text 88 Stories Wisdom Ancient Chinese works of Andy Chow 2015 may be concluded that: 1) There are 6 types of narrative texts 1) The text narrative form eksemplum, 2) Narrative text in the form of a fairy tale, 3) text narrative form of the legend, 4) Narrative text in the form of adventurers , 5) narrative text form pantasi, 6) and narrative texts in the form of fables and can be implemented in learning Indonesian in the junior class VIII in accordance with core competencies KI-3 Understand and apply knowledge (factual, conceptual, procedural) by curiosity about science, technology, arts, culture-related phenomena and events looking eyes, KI-4: Processing, menyaji, and reasoning in the realm of the concrete (using, parse, compose, modify, and make) and the realm of the abstract (writing, reading, counting, drawing, and writing) in accordance with the learned in school and other sources in the same angle of view of the theory and KD 3.1: Understand text moral stories / fables, reviews, discussion, stories prosedu, stories and biographies either through oral or written, KD 4.1 Capturing meaning of the text moral story / fable, reviews, discussions, procedures stories, biographies and stories both orally and in writing. In Acts 88 Wisdom Texts Ancient China Chow Andy works in 2015 there were moral that can be applied in everyday life by learners. Keywords: teaching materials, narrative texts, and the study of texts 88 Ancient Chinese Wisdom Story